2014
DOI: 10.1007/s00277-014-2211-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma patients with low proportion of circulating plasma cells had similar survival with primary plasma cell leukemia patients

Abstract: The common features shared by primary plasma cell leukemia (pPCL) and multiple myeloma (MM) with circulating plasma cells (CPCs) are peripheral blood invasion and expansion of plasma cells independent of the protective bone marrow (BM) microenvironment niche. However, few studies have addressed the relationship between pPCL and MM with CPCs. Here, we quantitated the number CPCs by conventional morphology in 767 patients with newly diagnosed MM; their clinic features were compared with those of 33 pPCL cases. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 26 publications
2
85
0
Order By: Relevance
“…16 In that case, patients with circulating plasma cells constituted 14.1% of the overall series and had a median survival of 25 months. The results of the present study are consistent with the ominous prognostic impact of peripheral blood plasmacytosis; however, the definition of a high-risk group found was different; ≥2% circulating PCs in the study by An et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…16 In that case, patients with circulating plasma cells constituted 14.1% of the overall series and had a median survival of 25 months. The results of the present study are consistent with the ominous prognostic impact of peripheral blood plasmacytosis; however, the definition of a high-risk group found was different; ≥2% circulating PCs in the study by An et al .…”
Section: Discussionmentioning
confidence: 91%
“…The presence of circulating PCs, identified by cytology, 16 multiparameter flow cytometry 17,18 or slide-based immunofluorescence, 19 is also associated with a worse prognosis in myeloma patients not fulfilling the criteria of PCL. The presence of circulating PCs is also a risk factor of progression to active disease in patients with monoclonal gammopathy of undetermined significance 20 and smoldering MM.…”
Section: Introductionmentioning
confidence: 99%
“…CTCs are considered an unfavourable prognostic factor and indicate an aggressive form of the disease (An, et al 2015, Paiva, et al 2013), and therefore detecting CTCs can be a powerful prognostic tool for MM (Peceliunas, et al 2012). We have previously shown that CTCs derive from a hypoxic sub-population that intravasated from the BM to the circulation and have enhanced homing (thus metastasis) to new BM niches (Azab, et al 2012a, Azab, et al 2013, Muz, et al 2015, Muz, et al 2014a, Muz, et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In MM, circulating tumour cells (CTCs) are considered an unfavourable prognostic factor and indicate an aggressive form of the disease (An, et al 2015, Paiva, et al 2013), and therefore detecting CTCs can be used as a powerful prognostic tool in this disorder (Peceliunas, et al 2012). In the clinical setting, CTCs in MM patients are detected using flow cytometry with CD138 (also termed SDC1) as the principle marker (An, et al 2015, Paiva, et al 2013, Peceliunas, et al 2012); however, recent studies suggest the presence of circulating clonal B-cells in MM that do not express CD138 (Thiago, et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation